2014
DOI: 10.4103/2249-4863.148131
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on menstrual hygiene among urban and rural adolescent girls of West Bengal

Abstract: Background:Menstruation is a normal physiological process to the females but sometimes it is considered as unclean phenomenon in the society.Objectives:To compare the perceptions of different aspects of menstrual hygiene between adolescent girls of rural and urban area.Materials and Methods:A community-based cross-sectional study was conducted from April 2013 to September 2013 in urban and rural area of South 24, Paraganas, West Bengal among 541 adolescent school girls in the age group of 13–18 years. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(129 citation statements)
references
References 5 publications
12
98
2
Order By: Relevance
“…9 Another study conducted by Baishakhi et al reported that only 36% girls in urban areas and 54.88% girls in rural areas use homemade sanitary napkins and reused the same in subsequent period. 10 It was observed in this study that 44.67% girls believed it to be a physiological process. However, studies conducted by Gupta et al, Teketo et al, Shamima et al reported that menstruation is believed to be normal physiological process by 86.25%, 57.89%, 72.8% girls respectively.…”
Section: Resultsmentioning
confidence: 86%
“…9 Another study conducted by Baishakhi et al reported that only 36% girls in urban areas and 54.88% girls in rural areas use homemade sanitary napkins and reused the same in subsequent period. 10 It was observed in this study that 44.67% girls believed it to be a physiological process. However, studies conducted by Gupta et al, Teketo et al, Shamima et al reported that menstruation is believed to be normal physiological process by 86.25%, 57.89%, 72.8% girls respectively.…”
Section: Resultsmentioning
confidence: 86%
“…12 In our study, educational status of majority of the parents of rural as well as urban subjects was found to be high school. Mokhasi et al, in their study in Karnataka among adolescent girls reported a literacy rate of 47.3% and 83.6% among mothers in rural and urban areas respectively, while Paria et al, in their study found 31.63% and 5.26% mothers with secondary school qualification in urban and rural areas respectively.…”
Section: Demographic Charactersmentioning
confidence: 89%
“…Mokhasi et al, in their study in Karnataka among adolescent girls reported a literacy rate of 47.3% and 83.6% among mothers in rural and urban areas respectively, while Paria et al, in their study found 31.63% and 5.26% mothers with secondary school qualification in urban and rural areas respectively. 12,13 Our study also revealed that majority of the rural subjects belonged to families which were below poverty line (BPL), while majority of the urban subjects belonged to families which were above poverty line (APL). Thakre et al, in a similar study in Nagpur (Maharashtra) also found 40.3% of the girls belonging to families which were below poverty line.…”
Section: Demographic Charactersmentioning
confidence: 90%
“…6 Paria et al in rural and urban school of west Bengal among girls of 13-18 years reported the mean age of menarche as 12.24±0.7261. 7 Barthalakshmi et al conducted a school based cross sectional study in Chidambaran on girls from class 8th to 12th with a mean age of menarche was 12.9±1.2 years. 8 Verma et al in a higher secondary school in Varsnasi with maximum number of girls in 15-16 years of age (57.5%) reported 12.98±0.77 years as the mean age of menarche.…”
Section: Discussionmentioning
confidence: 99%